Generalized warped product submanifolds of Lorentzian concircular structure manifolds - Tanumoy Pal; Ibrahim Al-Dayel; Meraj Ali Khan; Biswabismita Bag; Shyamal Kumar Hui; Foued Aloui (AIMS Mathematics, 2024)
We began by considering invariant, anti-invariant, proper slant, and pointwise slant submanifolds of a Lorentzian concircular structure manifold. Subsequently, we explored two distinct categories of warped product submanifolds. The first category encompassed the fiber submanifold as an anti-invariant submanifold, while the second category included the fiber submanifold as a pointwise slant submanifold. We established several fundamental results concerning these submanifold classes. Additionally, we demonstrated the existence of such submanifold classes through specific examples. Moreover, we derived inequalities for the squared norm of the second fundamental form.